Literature Survey on Maharashtra State Transport Buses and RFID (International Journal of Engineering and Computer Science, 2017)
In this paper, we are representing the literature survey on Maharashtra State Transport Buses and RFID. Most of the part of Maharashtra State is covered by Maharashtra State Transport Buses. It has been serving more than 70 lacks passengers daily. There is a very wide network of M.S.R.T.C. across Maharashtra. But on the other side M.S.R.T.C. is facing many problems like low load factor, high bus staff ratio and many other. Radio Frequency Identification (RFID) is one of the emerging technologies which can be used for vehicle tracking and for some other purposes. This paper deals with some basic information about RFID and problems faced by passengers travelling by State Transport buses.